Social Networking Media: A Newer Approach to Increase Awareness Against Tobacco Chewing - Gajera, Chirag; Malaviya, Shivangi; Patel, Umang; Bavarva, Neha; Patel, Manan; Mehta, Shreyash (National Journal of Community Medicine, 2014)
Background: Facebook is the most famous social networking website with more than 1.6 billion active users. This study which involves active participation and evaluation of responses to see it’s usefulness in planning advertisement for future media campaigns and intervention using social networking sites. Method: This was an interventional study, where intervention was done by providing health related message about tobacco chewing. The study was designed in two phases: 1) involvement phase 2) study phase Result: Total 840 users “Liked” the page, and participated in the study. There were females (29.2%) and males (57.1%) from the age group of 15-25 years. The proportion of the participants who liked the page were from Gujarat 31% followed by Delhi 20% and Maharashtra 17%. The percentage of reach for images was 76.3% followed by 69.4% for status update , 54.5% for video, 47.1% for slogan and message and for web links 30.6%. Total 71% of the users had clicked for images, 35% of the users had clicked for video, 22% users had clicked for status update, 16% of the users had any clicked for slogan and messages and 12 % of the users had clicked for web links. Conclusion: Facebook has been found highly effective in transmitting messages to health consumers, especially among the youngsters. So information regarding tobacco addiction and outcomes of tobacco chewing can be communicated effectively through Facebook through intense messages.